Penerapan Terapi Okupasi Memasak: Studi Kasus pada Pasien dengan Masalah Keperawatan Gangguan Persepsi Sensori Halusinasi Pendengaran - Iffah Amirotul Umah; Wita Oktaviana; Joko Purnomo (CV. Global Health Science Group, 2025)
The present study aims to analyze paradigm shifts in the philosophy of science for health promotion through a systematic literature review spanning the period of 2017–2025. This review adhered to the PRISMA 2020 guidelines and employed a narrative-thematic analysis of eight articles retrieved from five reputable international databases (Scopus, PubMed, ScienceDirect, SAGE, and Wiley). Quality appraisal was conducted using the Critical Appraisal Skills Programme (CASP) and the Joanna Briggs Institute (JBI) Checklist. Sixty-eight articles met the criteria for full-text reading, with eight articles passing the final selection based on the defined criteria. The findings indicate that the paradigm of health promotion has shifted from a biomedical-positivistic approach toward a paradigm that is pluralistic, reflective, and humanistic. The thematic analysis yielded four main themes: the shift from the biomedical paradigm toward pluralistic epistemology, the importance of context and mechanisms in the critical-realist approach, epistemic justice and ethical reflection in knowledge production, and community and social resilience as the basis of the new paradigm. This shift suggests that modern health promotion no longer focuses solely on technical interventions but on the construction of knowledge that is contextual, equitable, and rooted in human values. These findings are expected to form the basis for developing more participatory and inclusive health promotion policies and practices.